Aplikasi Nilai-nilai Jurnalisme Warga pada Radio Komunitas - A. Darmanto (Jurnal Komunikasi, 2007)
This article begins from the thesis that citizen journalism values are the most genuine democratization shape in human being history. Citizen journalism values application, therefore, hare to be done in order to touch the grass root community that have no access to articulate their voice (voiceless). Citizen journalism values application in community radio needs many parts synergy.